The Technological Singularity: The New Beginning or End of Human Civilization - Fajar Nur Bahri; Andhara; Heny Fadillah; Sukma Mulia; Suwandi Mikail Siagian (ISNU Nine-Star Multidisciplinary Journal, 2025)
Technological singularity refers to the point at which artificial intelligence (AI) surpasses human intelligence, creating fundamental changes in civilization. This concept involves the exponential acceleration of technological development with significant social, economic and ethical impacts. This research aims to explore singularity as an opportunity or threat to human existence. Through a literature-based qualitative approach, philosophical analysis is used to understand fundamental issues related to ethics, ontology, and the relationship between humans and technology. Singularity has the potential to be a new beginning by enabling the integration of technology and human values, as in the concept of Society 5.0. However, challenges such as technology access gaps, algorithm bias, and misalignment of goals between humans and AI can lead to social dystopia. By examining the relationship between humans and technology, this research provides a critical basis for policy making oriented towards sustainability and prosperity in the era of technological singularity. The results of this research provide new insights into how the singularity can profoundly shape the future of human civilization.